(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article aimed to use the taxonomy of Bloom, Marzano and Kendall applied to rational numbers, decimals, triangles, perimeters and areas. Determining the objective, level and domain in each thematic content.